Alpha amylase activity and its relation with the falling number in experimental strains of triticale and tricepiro with potential use in the production of bioethanol (Semiárida, 2021)
In the present work, the activity of alpha amylase enzymes and the Falling Number (FN) were determined in flours from ten experimental strains of triticeas cultivated in the Experimental Field of the Faculty of Agronomy, National University of La Pampa, Argentina. The conversion from FN to the Liquefaction Number (LN) was performed to obtain the linearity of the relationship with alpha amylases. The degree of association of the activity of the alpha amylase enzymes with the values of FN and LN was evaluated. Genetic variability in amylase activity was found between the lines studied. Some genotypes showed high activity of the alpha amylases enzymes making them suitable for their use in the production of bioethanol. A highly significant Pearson correlation (p
Keywords: Amylase activity; falling number; liquefaction number; triticeas flour